2007
DOI: 10.3748/wjg.v13.i38.5096
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors associated with pancreatic fistula after distal pancreatectomy, which technique of pancreatic stump closure is more beneficial?

Abstract: AIM:To identify risk factors related to pancreatic fistula in patients undergoing distal pancreatectomy (DP) and to determine the effectiveness of using a stapled and a sutured closed of pancreatic stump. METHODS:Sixty-four patients underwent DP during a 10-year period. Information regarding diagnosis, operative details, and perioperative morbidity or mortality was collected. Eight risk factors were examined. RESULTS:Indications for DP included primary pancreatic disease (n = 38, 59%) and non-pancreatic malign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
82
3
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(88 citation statements)
references
References 24 publications
(38 reference statements)
1
82
3
2
Order By: Relevance
“…Another fact that we found to be significant Several authors state that the texture of the pancreatic parenchyma is an important risk factor associated with the development of post-operative pancreatic fistula. 3,12,13 Fibrotic pancreatic tissue is believed to be less likely to leak as compared to soft pancreatic parenchymal tissue, as long as the continuity of the main pancreatic duct is not compromised. Due to the retrospective nature of our study, we were unable to include pancreatic texture as a variable in our analysis as we found that it was not consistently reported in the operative reports and medical records that were reviewed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another fact that we found to be significant Several authors state that the texture of the pancreatic parenchyma is an important risk factor associated with the development of post-operative pancreatic fistula. 3,12,13 Fibrotic pancreatic tissue is believed to be less likely to leak as compared to soft pancreatic parenchymal tissue, as long as the continuity of the main pancreatic duct is not compromised. Due to the retrospective nature of our study, we were unable to include pancreatic texture as a variable in our analysis as we found that it was not consistently reported in the operative reports and medical records that were reviewed.…”
Section: Discussionmentioning
confidence: 99%
“…Obesity, patient age, trauma, malignancy, duct obstruction and texture of the pancreatic parenchyma have all been implicated as potential risk factors 9,12 . However, surgical technique is also considered an important risk factor for the development of pancreatic fistula 9 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main problems after surgery of the pancreas are pancreatic fistula, sterile collection, abscess and wound disruption, all of them believed to be due to pancreatic leakage from the stump and reaching an incidence rate of 11-27% [4,7,8,13,15,20,23]. Stapler transection of the pancreas body is the most preferred in laparoscopic pancreatic surgery [5,6,9,13,24,25].…”
Section: Discussionmentioning
confidence: 99%
“…1,10,20 We can speculate that this risk is in part increased by the crushing of the pancreatic tissue and the consequent destruction of small pancreatic ducts due to the pressure applied by a mechanical stapler before cutting and staple application. 11 In our model no pressure is applied to the pancreatic tissue, and only the previously sealed parenchyma are then cut by the device, thus avoiding the rupture of small pancreatic ducts before sealing.…”
Section: Discussionmentioning
confidence: 99%